"Understanding a fury in your words": The effects of posting and viewing electronic negative word-of-mouth on purchase behaviors. (January 2016) - Kim, Su Jung; Wang, Rebecca Jen-Hui; Maslowska, Ewa; Malthouse, Edward C.
Abstract: Marketing scholars and practitioners have long recognized that the power of electronic negative word-of-mouth (e-NWOM) can influence brand revenues and firm performance, but most previous studies have only examined the effect of viewing. This study is one of the initial attempts to test the effects of e-NWOM on both posters and viewers. We also test the moderating effects of company usefulness and company apology in a separate study. Using an observational dataset that contains NWOM viewing and posting records and customers' purchase transactions from a real company, Study 1 finds that viewing e-NWOM has a negative effect on subsequent purchases, whereas posting e-NWOM has a positive interaction effect with company usefulness. Study 2 shows that a company's public apology has a positive effect on viewers, but not posters. We conclude with the theoretical, methodological, and managerial implications of e-NWOM and webcare research. Highlights: We distinguish the effects of posting and viewing e-NWOM on purchase behavior. We identify two moderators of e-NWOM and test their effects in two studies. Viewing e-NWOM decreases subsequent purchases. Posting e-NWOM has a positive interaction effect with company usefulness. Company apology only works for e-NWOM viewers, not posters.